Is it possible to constantly and accurately monitor blood sugar levels, in people with Type 1 diabetes, with a discrete device (non‐invasive or invasive)?. Issue 4 (13th March 2019) - Avari, P.; Reddy, M.; Oliver, N.
Abstract: Real‐time continuous glucose monitors using subcutaneous needle‐type sensors continue to develop. The limitations of currently available systems, however, include time lag behind changes in blood glucose, the invasive nature of such systems, and in some cases, their accuracy. Non‐invasive techniques have been developed, but, to date, no commercial device has been successful. A key research priority for people with Type 1 diabetes identified by the James Lind Alliance was to identify ways of monitoring blood glucose constantly and accurately using a discrete device, invasive or non‐invasive. Integration of such a sensor is important in the development of a closed‐loop system and the technology must be rapid, selective and acceptable for continuous use by individuals. The present review provides an update on existing continuous glucose‐sensing technologies, and an overview of emergent techniques, including their accuracy and limitations. What's new?: One of 10 key research priorities identified by the James Lind Alliance Type 1 diabetes Priority Setting Partnership was to investigate whether it is possible to monitor blood sugar levels constantly and accurately with a discrete device (non‐invasive or invasive). This paper provides an overview of the latest glucose‐sensing techniques, currently marketed products and their accuracy. To date, no device based on a non‐invasive technique has successfully reached the commercial market. We review the technological challenges faced, clinical impact and future directions in continuous glucose monitoring.